Políticas linguísticas de famílias multilíngues em Foz do Iguaçu-PR - Oliveira, Renata Alves de (2024)
This thesis investigates the linguistic policies of multilingual families residing in Foz do Iguaçu – PR, located at the tri-national border of Brazil, Paraguay, and Argentina. The focus is on the management of languages present in the repertoires of these families, considering the dominant linguistic constellations and parental linguistic ideologies. The study analyzes how parents navigate the confluence of languages in their daily lives and promote the linguistic development of their children. Adopting an interdisciplinary approach that integrates Linguistics, Sociolinguistics, Geography, and Migration Studies, the research examines family language policies (FLP) as reflections of parental decisions regarding the preservation and management of heritage and additional languages in a context marked by mobility and cultural diversity. It observes identity and cultural dynamics, highlighting how these policies manifest in familial micro-spheres and impact the identity formation of children. The qualitative and interpretative methodology is based on a sociolinguistic mapping of families from diverse origins, selected through non-probabilistic network sampling (snowballing) residing in Foz do Iguaçu. The triangulation of ideologies, management, and linguistic practices reveals defense and coping mechanisms utilized by families to overcome the challenges of multilingualism. The results indicate that these families, generally homogeneous in terms of social class and education, devise tactics to balance the preservation of heritage languages—viewed as a means of cultural maintenance—with linguistic adaptation to the host country. Furthermore, they encourage the learning of additional languages, such as English, which is deemed essential for their children's educational and professional development. It is confirmed that the border region fosters multilingualism by serving as a dynamic space where cultures and languages coexist and are valued. Family language choices reflect a combination of emotional and ideological aspects, constituting a continuous effort to protect culture while ensuring integration into society. The concept of "linking-place" is proposed to describe the spatial and temporal experiences of multilingual families, where heritage languages are preserved and transmitted. This concept bridges generations, integrating past, present, and future, and shaping identities, memories, histories, and cultural practices. It is concluded that family language policies, specific to each group, serve as an identity support in contexts of migration and borders, reaffirming multilingualism as a practice of resistance and cultural preservation.